2006
DOI: 10.1016/j.clinph.2005.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Sources of cortical rhythms change as a function of cognitive impairment in pathological aging: a multicenter study

Abstract: The present functional data on large populations support the 'transitional hypothesis' of a shadow zone across normality, pre-clinical stage of dementia (MCI), and AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

48
275
4
8

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 275 publications
(335 citation statements)
references
References 153 publications
48
275
4
8
Order By: Relevance
“…Diffuse low frequent activity on quantitative EEG is seen in AD and correlates with disease stage [1,11,44]. Increase of relative theta power by itself or in combination with changes in other frequencies has in several studies differentiated early forms of AD from controls, and has showed intermediate characteristics in MCI [11,29,30,33,44,48].…”
Section: Introductionmentioning
confidence: 99%
“…Diffuse low frequent activity on quantitative EEG is seen in AD and correlates with disease stage [1,11,44]. Increase of relative theta power by itself or in combination with changes in other frequencies has in several studies differentiated early forms of AD from controls, and has showed intermediate characteristics in MCI [11,29,30,33,44,48].…”
Section: Introductionmentioning
confidence: 99%
“…The most stable pattern of EEG activity in MCI patients is defined by an increase in theta accompanied by a decrease of alpha and beta power, which correlates with APOE genotype, and hippocampal volumes (Babiloni et al 2006b(Babiloni et al , c, 2009Grunwald et al 2002;Prichep et al 2006). When the progression to AD was investigated, alpha and theta relative power in left temporooccipital derivation correctly classified 85 % of MCI subjects who would suffer dementia .…”
Section: Introductionmentioning
confidence: 99%
“…Causal relationships between the neural sources of EEG-alpha rhythm were estimated by using measurements of functional directionality based on Granger causality [Kaminski et al, 2001], and the significance of directional strength evaluated with surrogated data. Since previous evidence has shown that the presence of the allele ε4 in the apoliprotein E (ApoE) not only increases the risk of developing AD [Caselli et al, 2007;Wang et al, 2002;Corder et al 1993] but also correlates with changes in the cortical dynamics of alpha rhythm [Babiloni et al, 2006], both probability of source activation and direction of synaptic flow between EEG-alpha sources were compared between carriers and non-carriers of the allele ε4 in controls and MCI groups.…”
mentioning
confidence: 99%
“…EEG measurements emerge from summated excitatory and inhibitory postsynaptic potentials primarily generated by synaptic activity of large pyramidal neurons [Lopes da Silva and Van Rotterdam, 1993]. Among EEG oscillations, the alpha rhythm has been reported to be typically affected in AD patients [Huang et al, 2000;Osipova et al, 2005;Babiloni et al, 2006]. Alpha waves are intrinsically generated by synaptic networks of neocortical pyramidal neurons in layer 5 by means of the tonic activation of N-methyl-D-aspartate receptors with endogenous glutamate [Silva and Connors, 1991].…”
mentioning
confidence: 99%